Hybrid multimodal imaging synthons for chemoselective and efficient biomolecule modification with chelator and near-infrared fluorescent cyanine dye - Hübner, Ralph; Kiedrowski, Valeska von; Benkert, Vanessa; Wängler, Björn; Schirrmacher, Ralf; Krämer, Roland; Wängler, Carmen (Pharmaceuticals, 2020)
The development of hybrid multimodal imaging synthons (MIS), carrying in addition to a chelator for radiometal labeling also a near-infrared (NIR) fluorescent cyanine dye was the aim of this work. The MIS should be introducible into biomolecules of choice via an efficient and chemoselective click chemistry reaction. After chemical optimization, a successful synthetic strategy towards such hybrid MIS was developed, based on solid phase-based synthesis techniques and applying different near-infrared fluorescent cyanine dyes. The developed hybrid agents were shown to be easily introducible into a model homobivalent peptidic gastrin-releasing peptide receptor- (GRPR)-specific carrier without forming any side products and the MIS as well as their bioconjugates were radiolabeled with the positron-emitter 68Ga3+. The hybrid multimodal agents were characterized with regard to their logDs, GRPR target affinities and photophysical characteristics. It could be shown that the properties of the bioconjugates were not per se affected by the introduction of the MIS but that the cyanine dye used and specifically the number of comprised negative charges per dye molecule can have a considerable influence on target receptor binding. Thus, the molecular toolbox described here enables the synthesis of tailored hybrid multimodal imaging synthons for biomolecule modification, meeting the specific need and envisioned application of the combined imaging agent.
Gesehen am 16.11.2020